First record of the genus Disholcaspis Dalla Torre & Kieffer (Hymenoptera: Cynipidae: Cynipini) in the Neotropics, with description of two new species from Panama - Medianero, Enrique; Nieves-Aldrey, José Luis (Zootaxa, 2011)
Two new species of Disholcaspis Dalla Torre & Kieffer 1910, Disholcaspis bettyannae and D. bisethiae (Hymenoptera: Cynipidae: Cynipini) are described from Panama. The two new species induce galls on Quercus bumelioides Liebm. and Q. lancifolia Schledl & Cham. (Fagaceae, sect. Quercus, White Oaks). Diagnostic characters, gall descriptions, distribution, biological data, as well as inquiline and parasitoid associated community data of the new species are given. The new species represent the first records of the genus Disholcaspis from the Neotropical region.